Association between IgG4 Autoantibody and Complement Abnormalities in Systemic Lupus Erythematosus. (11th August 2016) - Pan, Qingjun; Guo, Linjie; Wu, Jing; Cai, Jun; Liao, Huanjin; Lan, Qiaofen; Peng, Yanxia; He, Yiming; Liu, Hua-feng
Abstract : In order to investigate the association between IgG4 autoantibody and complement abnormalities in systemic lupus erythematosus (SLE), 72 newly diagnosed SLE patients, 67 rheumatoid arthritis (RA) patients, and 41 healthy normals were employed. Serum levels of antinuclear IgG4 and IgG4-specific IgM-rheumatoid factor (RF) were measured, and the correlations between serum levels of antinuclear IgG4 and several clinical parameters were analyzed. Also, the levels of IgG subclasses, C1q, and C3 deposition in lupus nephritis (LN) were detected. The results showed that serum levels of antinuclear IgG4 were higher in SLE patients relative to healthy normals (P < 0.01 ). Serum levels of antinuclear IgG4 in SLE patients were positively correlated with serum levels of total IgG4, albumin, and C3 (r = 0.61, P < 0.05 ;r = 0.40, P < 0.05 ; andr = 0.54, P < 0.05, resp.) and negatively correlated with 24-hour urinary protein (r = 0.49, P < 0.05 ). Serum levels of IgG4-specific IgM-RF were higher in RA patients than in SLE patients (P < 0.001 ). Also, the ratio of the deposition score for IgG4/(IgG1 + IgG2 + IgG3 + IgG4) was negatively correlated with the score for C1q and C3 deposition in LN (r = 0.34, P < 0.05 ;r = 0.51, P < 0.01, resp.). In summary, the IgG4 autoantibody may dampen the inflammatory response in SLE, thus maybe providing a novel therapeutic target for SLE.